Feminitas yang Dirasakan: Perempuan Bekerja dalam Pekerjaan yang Didominasi Laki-Laki - Nadia Revania Bima; Intan Primadini (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2023)
Patriarchal society significantly affects how people interpret gender In the Indonesian, which leads to segregation and gender stereotypes in the workplace.Current development, women are entering fields like mining and construction that were formerly dominated by men. This study seeks to understand how women perceive their femininity when working in environments where men predominate. The research method is interpretive phenomenological analysis (IPA), which uses a qualitative and explorative approach in line with the constructivist paradigm. The information gathered from interviews was analyzed using Smith, Flowers, and Larkin's (2009) data analysis techniques. The findings indicate that women who work in professions where men predominate regard their femininity as a combination of traditional femininity, new femininity, and adopted male traits as a means of adjusting to the workplace. This leads us to the conclusion that femininity is currently changing and that women today tend to express themselves more freely.